Socio-Economic Impacts of Fruit Crop Production in the Mungo Corridor, Littoral Region, Cameroon - Tionwa, Gwladys Diane Fosso; Fombe, Lawrence Fon; Samba, Gideon (American Journal of Food Sciences and Nutrition, 2024)
Purpose: Agriculture, particularly fruit crop production, serves as a vital driver of economic growth worldwide. In Cameroon, the Mungo Corridor plays a substantial role in the agricultural sector, particularly in fruit crop production. This study aims to assess the socio-economic impacts of fruit crop production within the Mungo Corridor, a region known for cultivating bananas, pineapples, and mangoes. By evaluating the economic contributions and challenges, the study seeks to provide insights for policies that could enhance the sustainability and development of fruit production in the area. The study adopted a multi-stage sampling technique to select respondents and resource persons. Materials and Methods: Data collection involved the use of structured and pre-tested questionnaires along with an interview guide. Quantitative data was analyzed using the Statistical Package for Social Sciences (SPSS) version 16.0 and Microsoft Excel, while qualitative data from interviews was subjected to thematic analysis. Six subdivisions from the Mungo Division were purposely chosen to represent the agricultural activities within the region. Findings: The study confirms that fruit crop production has significant socio-economic benefits in the Mungo Corridor. Over a 10-year period, banana production reached 195,000 tons, while pineapple production rose from 6,543 tons in 2012 to 28,141 tons in 2022. Papaya production increased from 36 tons to 86 tons during the same period. The income from fruit sales enabled stakeholders to develop socio-economic activities, fostering regional development. Fruit crop production contributed to the construction of 12 schools (primary and secondary), 21 health centers, the rehabilitation of 8 fruit markets, 3 bus stations, and growth in the informal sector. However, the study also identified several challenges with Farmers face limited access to markets. Poor infrastructure affects production and distribution. The looming threat of climate change presents long-term risks to fruit farming. Implications to Theory, Practice and Policy: To address the challenges and ensure sustainable fruit crop production in the Mungo Corridor, the study recommends the implementation of policies that promote local products and support farmers through market access initiatives. Invest in transport, storage, and market infrastructure to improve efficiency. Develop interventions to mitigate the impact of climate change on fruit production and strengthen cooperation among farmers, government, and private actors to maximize the benefits of fruit crop production and foster sustainable development. By highlighting the essential role of fruit farming in the socio-economic development of the Mungo Corridor, the study emphasizes the need for renewed efforts to support the sector and enhance its contributions to regional growth.